2024
DOI: 10.21037/tbcr-23-43
|View full text |Cite
|
Sign up to set email alerts
|

Implications of tumor-infiltrating lymphocytes in early-stage triple-negative breast cancer: clinical oncologist perspectives

Mahira Lopes Rosa,
Tomas Reinert,
Maiane Maria Pauletto
et al.

Abstract: Breast cancer (BC) is the most common neoplasm in women worldwide and one of the leading causes of female death. The triple-negative subtype, characterized by the absence of hormone receptor (HR) and human epidermal growth factor receptor 2 (HER2), tends to occur in younger patients, be more aggressive and less differentiated. Furthermore, this subtype is considered the most immunogenic and associated with higher levels of tumor cell infiltration, mainly lymphocytes. Tumor-infiltrating lymphocytes (TILs) play … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 83 publications
0
1
0
Order By: Relevance
“…We used a state-of-the-art multiplex immunofluorescence technology and artificial intelligence (AI) software algorithms for the simultaneous quantitative analysis of relevant immune cells, and showed differential expression based on tumor characteristics and significant correlation with overall survival and patient’s outcome. Several studies found a strong linear relationship between an increase in tumor-infiltrating lymphocytes (TILs) and improved recurrence-free survival for triple-negative and HER2-positive breast cancers [ 31 , 32 ]. Higher levels of TILs correlated in all molecular subtypes with increased rates of pathologic complete response to neoadjuvant therapy [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…We used a state-of-the-art multiplex immunofluorescence technology and artificial intelligence (AI) software algorithms for the simultaneous quantitative analysis of relevant immune cells, and showed differential expression based on tumor characteristics and significant correlation with overall survival and patient’s outcome. Several studies found a strong linear relationship between an increase in tumor-infiltrating lymphocytes (TILs) and improved recurrence-free survival for triple-negative and HER2-positive breast cancers [ 31 , 32 ]. Higher levels of TILs correlated in all molecular subtypes with increased rates of pathologic complete response to neoadjuvant therapy [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%